Case studies of up-cycling of partially crystallized ceramic waste in highly porous glass-ceramics. (20th November 2020) - Monich, P. Rabelo; Romero, A. Rincon; Rambaldi, E.; Bernardo, E.
Highlights: Valorization of polishing residue or vitrified asbestos-containing waste. Glass-ceramic foams by alkali activation, gel-casting and sintering. Highly porous materials with high strength-to-density ratio were obtained. Reduction of process costs by minimizing additives and processing temperatures. Soda-lime glass addition favored densification and control of crystal phases. Abstract: Highly porous glass-based materials represent a solution for thermal insulation. However, the manufacturing costs still affect their extensive use. The present investigation proposes savings in the production of foams by use of discarded materials, such as polishing residue or vitrified asbestos-containing waste, minimizing additives and processing temperatures. Aqueous suspensions of powders, mixed with soda-lime glass, underwent progressive gelation due to alkali activation. An extensive foaming was determined by mechanical stirring, with the help of a surfactant. Finally, a firing step yielded foams exhibiting excellent strength-to-density ratios, due to densification and control of crystal phases, both supported by the glass addition.